2014
DOI: 10.1590/0004-282x20140113
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of basilar invagination in patients with tonsillar herniation ? a case control craniometrical study

Abstract: A retrospective case-control study based on craniometrical evaluation was performed to evaluate the incidence of basilar invagination (BI). Patients with symptomatic tonsillar herniation treated surgically had craniometrical parameters evaluated based on CT scan reconstructions before surgery. BI was diagnosed when the tip of the odontoid trespassed the Chamberlain's line in three different thresholds found in the literature: 2, 5 or 6.6 mm. In the surgical group (SU), the mean distance of the tip of the odont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 13 publications
(24 reference statements)
1
15
0
Order By: Relevance
“…A similar correlation was referred to by Joaquim et al 22 , who demonstrated that the presence of platybasia and a decreased clivus seem to favor a protrusion of the cervical spine to the inside of the skull base (basilar invagination) 24 . Previous studies have already hypothesized that the presence of platybasia may be associated with compression of posterior fossa structures by mechanical opposition to the apex of the odontoid process 1,4,5 .…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…A similar correlation was referred to by Joaquim et al 22 , who demonstrated that the presence of platybasia and a decreased clivus seem to favor a protrusion of the cervical spine to the inside of the skull base (basilar invagination) 24 . Previous studies have already hypothesized that the presence of platybasia may be associated with compression of posterior fossa structures by mechanical opposition to the apex of the odontoid process 1,4,5 .…”
Section: Discussionsupporting
confidence: 77%
“…The WBA has varied broadly, with one reported average of 115.41° (±8.45°) for Netto et al 19 There is still no consensus over the upper limit for DOCL values, which range from 2.0 to 6.6 mm 1,20,21 . This difference is not insignificant when compared to the small dimensions of CVT and hence could lead to considerable changes in specificity in the diagnosis of basilar invagination, as well as in the estimated prevalence 11,22 . Taking into consideration the DOCL upper limit of 2 mm 20 , more than half of the participants in this study would be diagnosed with basilar invagination, which would be unlikely for individuals who come to imaging services by spontaneous demand.…”
Section: Discussionmentioning
confidence: 99%
“…In the most primitive hominins, such as in the Homo erectus, the basal angle was estimated to be much higher than, for instance, in Homo sapiens, suggesting its importance to the modern shape of the human skull base 7,10,11 . In patients with CI a higher incidence of platybasia and shortness of clivus has been described by some authors 2,12,13 . Karagöz et al 13 performed a craniometrical study in 22 patients with CI, comparing them with 21 normal subjects as a control group.…”
Section: Discussionmentioning
confidence: 86%
“…, Andrei Fernandes Joaquim 1,3 Chiari I (CI) is one of the most common congenital craniocervical disorders and its diagnosed when there is tonsillar herniation into the foramen magnum of up to 3-5 mm 1,2 . The impaction of the tonsils at the level of the foramen magnum can lead to interruption of the cerebrospinal fluid flow and clinical symptoms, with upper cervical spine compression 2,3,4 .…”
mentioning
confidence: 99%
See 1 more Smart Citation